THE INTENSITY OF OXIDATIVE MODIFICATION OF PROTEINS AND PEROXIDATION OF LIPIDS IN THE BLOOD SERUM, BRAIN, LIVER AND PANCREAS TISSUES OF RATS WITH INSULIN RESISTANCE AND CONGENITAL IODINE DEFICIENCY - Stetsevyat, V. B.; Voronych-Semchenko, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The results of the study about the nature of oxygen-dependent processes in rats that were on a high-fructose diet for 8 weeks under conditions of adequate iodine supply and congenital iodine deprivation is presented in the article. The significant activation of peroxide oxidation of proteins (by increasing the aldo- and keto-derivates of a neutral nature) and lipids (increased of diene conjugates content and products, that are responsible to thiobarbituric acid) of animals with insulin resistance was found. An aggravating factor in the course of these processes is a congenital iodine deficiency. The changes of oxidative modification of proteins in animals with congenital iodine deficiency had multidirectional character, and processes of lipid peroxidation mainly increased. The most pronounced changes of the studied processes were observed in the liver and pancreas of animals with insulin resistance against the background of congenital iodine deficiency.